2013
DOI: 10.1042/bj20120627
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure, dynamics and binding studies of a family 11 carbohydrate-binding module from Clostridium thermocellum (CtCBM11)

Abstract: Non-catalytic cellulosomal CBMs (carbohydrate-binding modules) are responsible for increasing the catalytic efficiency of cellulosic enzymes by selectively putting the substrate (a wide range of poly- and oligo-saccharides) and enzyme into close contact. In the present study we carried out an atomistic rationalization of the molecular determinants of ligand specificity for a family 11 CBM from thermophilic Clostridium thermocellum [CtCBM11 (C. thermocellum CBM11)], based on a NMR and molecular modelling approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
2
8
0
2
Order By: Relevance
“…cellulovorans CbpA (1.67 µM −1 ) 28 . The binding efficiency of chimeric Dtur CelA towards the long chains of Avicel is consistent with the results of Viegas and collaborators 19 , who observed a higher affinity of Ct CBM11 for larger ligands when compared to those with the minimal length to fit the binding cleft. This difference is probably due to the presence of more contact points in larger oligosaccharides.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…cellulovorans CbpA (1.67 µM −1 ) 28 . The binding efficiency of chimeric Dtur CelA towards the long chains of Avicel is consistent with the results of Viegas and collaborators 19 , who observed a higher affinity of Ct CBM11 for larger ligands when compared to those with the minimal length to fit the binding cleft. This difference is probably due to the presence of more contact points in larger oligosaccharides.…”
Section: Resultssupporting
confidence: 90%
“…These data are in accordance with those reported previously: Dtur CelA temperature optimum was stated between 70 °C and 80 °C 6 . Concerning Ct CBM11, Viegas and collaborators observed that it does not change its structure at 25 °C and 50 °C, confirming its stability in this °T range; moreover, a closer contact between Ct CBM11 and cellohexaose was detected at 50 °C than 25 °C 19 . At the most acidic pH tested, chimeric Dtur CelA showed higher relative activity compared to the native form (20% vs 0%).…”
Section: Resultsmentioning
confidence: 87%
“…Cellulose binding by type‐A CBMs is mediated by a planar array of aromatic amino acids on their surface that form stacking interactions with the sugar rings of crystalline cellulose chains resulting in strong van der Waals interactions, thus stabilizing the structure. Although many structural studies using X‐ray1315 and solution NMR spectroscopy1618 were conducted on CBM proteins, only a few studies employed measurements of dynamics in these systems 1821…”
Section: Introductionmentioning
confidence: 99%
“…The atomistic model of the CtCBM11 (Clostridium thermocellum CBM11) was constructed using the reported NMR structure 2LR0 (Viegas et al, 2013). The blood iron-binding peptide was initially generated as a a-helix and attached to the C-terminal end of CtCBM11.…”
Section: Methodsmentioning
confidence: 99%